Mapping of Geosystem Services for Comprehensive Planning: A Case Study of Askersund Municipality - Gustafsson, Anja (My University)
The subsurface under our feet holds many 'invisible' qualities that are valuable to society, from geomaterials to flood mitigation and storage space. In Sweden, however, subsurface planning is rarely designed to account for these functions and instead often suffers from a “first come, first served” principle, which can hinder sustainable planning and lead to unnecessary costs and loss of value. The concept of Geosystem Services (GS), inspired by Ecosystem Services, has been developed to make these subsurface benefits more visible and support more informed planning decisions. Previous work by Lundin-Frisk (2025) has resulted in an indicator-based mapping methodology to visualize GS potential, which has been applied to support resilience planning in Malmö (the M-case). This master’s thesis presents a new case study which is inspired by the M-case but applied under the conditions of Askersund municipality. The aim is to evaluate the general improvement potential of GS maps and assess their suitability for supporting municipal comprehensive planning. The study's process consisted of four main steps. First, relevant geosystem services were selected, resulting in five prioritized services: ‘infiltration of stormwater’ for natural flood mitigation, ‘provision of groundwater’ for extraction on municipal scale, ‘bearing capacity’ regarding surface construction, ‘resistance to erosion’ regarding construction, and ‘provision of rock aggregates’ for concrete production. Second, indicators and data sources were identified or developed. Third, the services were mapped in QGIS, producing two map types for each service: Geophysical potential (G), representing the inherent capacity of the environment to supply the service, and Effective potential (E), representing the share of this capacity that is available and suitable for use. Finally, the maps were evaluated in a workshop with representatives from Askersund municipality to assess their usability and identify improvement opportunities. The results showed that the methodology overall was applicable to Askersund, although some adjustments were required. The results of the evaluation were generally positive and indicated that GS potential maps can function as a valuable complement for comprehensive planning, particularly as communicative support material in early planning stages. While the findings were considered representative for comprehensive planning in Askersund and suggests potential for broader application, the limited scale of the study still constrains broader generalisations to other municipalities and planners.